2019
DOI: 10.17475/kastorman.662699
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Artificial Neural Network Model to Minimize Power Consumption in the Milling of Heat-Treated and Untreated Wood

Abstract: Aim of study: The power consumption of machining operations is an important part of the total production cost. Therefore, in this study, an artificial neural network (ANN) model was developed to model the effects of treatment, rotation speed, cutting depth, and feed rate on power consumption in the wood milling process. Material and methods: A multilayer feed-forward ANN was employed for the prediction of power consumption. The accuracy of the model was assessed by performance indicators such as MAPE, RMSE, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Prommul et al [24] stated that ANN was as a satisfactory approach to predict SR. Besides, it was indicated that the ANN approach was an acceptable tool to predict power consumption in the wood milling process [17,22]. In this respect, it can be said that even similar better results were obtained with the literature in terms of the PEC.…”
Section: Annmentioning
confidence: 70%
See 4 more Smart Citations
“…Prommul et al [24] stated that ANN was as a satisfactory approach to predict SR. Besides, it was indicated that the ANN approach was an acceptable tool to predict power consumption in the wood milling process [17,22]. In this respect, it can be said that even similar better results were obtained with the literature in terms of the PEC.…”
Section: Annmentioning
confidence: 70%
“…The training of neural network stopped when there was no improvement in accuracy or loss on the validation set over a certain number of epochs. The mean square error (MSE) was used in the evaluation of the performance of ANN models, and it is given in Equation (2) [17]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations